Associations of changes in physical activity and sedentary time with weight recurrence after bariatric surgery: a 5-year prospective study - Sundgot-Borgen, Christine; Bond, D. S.; Sniehotta, Falko F.; Kvalem, I. L.; Hansen, B. H.; Bergh, I.; Rø, Ø; Mala, T. (International journal of obesity, 2023)
Increasing physical activity and limiting sedentary time may minimize weight recurrence after bariatric surgery. However, few studies have evaluated potential associations of objectively-measured physical activity and sedentary time with post-surgical weight recurrence over time.